ANALYSIS OF BUDGET REALIZATION AS A BASIS FOR ASSESSING THE EFFECTIVENESS AND EFFICIENCY OF THE FINANCIAL PERFORMANCE OF THE MAKASSAR CITY GOVERNMENT - Maulida Nurul Syahrani; M. Ridwan Tikollah; Hajrah Hamzah (KEUDA (Jurnal Kajian Ekonomi dan Keuangan Daerah), 2026)
This study aims to assess the effectiveness and efficiency of the financial performance of the Makassar City Government. The variables this study are the effectiveness and efficiency of the financial performance. The subject of this research is the budget realization report, while the research focus is on effectiveness and efficiency. Data collection techniques were carried out through documentation, literature review, and interviews. Data analysis was performed using descriptive quantitative analysis. The data used in this study are secondary data in the form of the Budget Realization Report of the Makassar City Government for the 2019-2024 fiscal years. The results of this study show that the financial performance of the City Government, when viewed from: 1) the level of effectiveness, shows a less stable trend. In the 2019 to 2021 period, financial performance was in the effective category, but from 2022 to 2024, it experienced a decline to the sufficiently effective category. This decrease was caused by the setting of ambitious budget targets that were not commensurate with the ability to realize them, creating a gap between the target and the actual revenue realization. 2) The level of efficiency consistently shows a sufficiently efficient result, remaining at a ratio below 100%, which indicates that there was no waste in the management of the expenditure budget. Although there were fluctuations, this reflects the careful adjustments made in the use of the regional expenditure budget.